The CONTINUITY MIDWIFERY CARE OF MRS. M, MRS.I, AND MRS. N IN MIDWIFERY INDEPENDENT PRACTICE LANGGENG SRI ASIH, S.ST AT DISTRICT OF PAGELARAN, PRINGSEWU REGENCY IN 2023: Indonesia - Elsa Surya (Jurnal Maternitas Aisyah (JAMAN AISYAH), 2023)
Lower back pain or low back pain in pregnancy is an unpleasant condition due to the growing uterus and increased body weight causing the muscles to work harder so that it can cause stress on the muscles and joints. Pregnancy exercise can provide benefits for maintaining and improving the physical health of pregnant women, improving blood circulation, reducing complaints of aches and pains including back pain during pregnancy, and preparing breathing, muscle and pelvic activity to face the birth process. Based on the above, the authors take the formulation of the problem in this report whether pregnancy exercise in third trimester pregnant women can reduce back pain in pregnant women? This final project report is in the form of a case study using the SOAP method of documentation. The subjects of this study were third trimester pregnant women, childbirth, postpartum, newborns, so that mothers can decide on family planning methods. In collecting data, it is done by using anamnesis, physical examination, cases are processed and analyzed. The results of the study showed that pregnancy care was provided by providing pregnancy exercise care to 3 pregnant women who experienced back pain during pregnancy. Of the three pregnancies that were followed, all patients were given intervention by doing pregnancy exercise to show a decrease in back pain. This was stated by the results of interviews with patients that back pain was reduced after doing pregnancy exercise and one patient said that sleep became better after doing pregnancy exercise.